Go backward to Integer ArithmeticGo up to TopGo forward to More Arithmetic |

- -2 = -<2
_{N}, 0_{N}> = <0_{N}, 2_{N}>. - (-2)+1 = (-<2
_{N}, 0_{N}>) + <1_{N}, 0_{N}> = <0_{N}, 2_{N}> + <1_{N}, 0_{N}> = I(0_{N}+1_{N}, 2_{N}+0_{N}) = I(1_{N}, 2_{N}) = <0_{N}, 1_{N}> = -<1_{N}, 0_{N}> = -1. - 2*3 = <2
_{N}, 0_{N}> * <3_{N}, 0_{N}> = I((2_{N}*_{N}3_{N}) + (0_{N}*_{N}0_{N}), (2_{N}*_{N}0_{N}) + (3_{N}*_{N}0_{N})) = I(6_{N}, 0_{N}) = <6_{N}, 0_{N}> = 6. - (-2)*3 = (-
<2
_{N}, 0_{N}>) * <3_{N}, 0_{N}> = <0_{N}, 2_{N}> * <3_{N}, 0_{N}> = I((0_{N}*_{N}3_{N}) + (2_{N}*_{N}0_{N}), (0_{N}*_{N}0_{N}) + (2_{N}*_{N}3_{N})) = I(0_{N}, 6_{N}) = <0_{N}, 6_{N}> = -<6_{N}, 0_{N}> = -6.

*Substituting and evaluating the definitions.*

Author: Wolfgang Schreiner

Last Modification: November 16, 1999